Heat distribution in rectangular fins using efficient finite element and differential quadrature methods - Basri, Shahnor; Fakir, Md. Moslemuddin; Mustapha, Faizal; Abang Abdul Majid, Dayang Laila; Jaafar, Abdul Aziz (Scientific Research Publishing, 2009)
Finite element method (FEM) and differential quadrature method (DQM) are among important numerical techniques used in engineering analyses. Usually elements are sub-divided uniformly in FEM (conventional FEM, CFEM) to obtain temperature distribution behavior in a fin or plate. Hence, extra computational complexity is needed to obtain a fair solution with required accuracy. In this paper, non-uniform sub-elements are considered for FEM (efficient FEM, EFEM) solution to reduce the computational complexity. Then this EFEM is applied for the solution of one-dimensional heat transfer problem in a rectangular thin fin. The obtained results are compared with CFEM and efficient DQM (EDQM), with non-uniform mesh generation). It is found that the EFEM exhibit more accurate results than CFEM and EDQM showing its potentiality.